Clinical and histologic features associated with lentigo maligna clearance after imiquimod treatment. (19th May 2022) - Kwak, R.; Joyce, C.; Werchniak, A. E.; Lin, J. Y.; Tsibris, H. C.
Abstract: Background: Imiquimod cream may be used as a non-surgical treatment for lentigo maligna or as adjuvant therapy following excision to decrease the risk of recurrence. Objectives: To evaluate histologic and clinical factors associated with clinical clearance of lentigo maligna treated with imiquimod. Methods: We performed a retrospective review of all patients diagnosed with lentigo maligna and treated with imiquimod between 1997 and 2019 at our academic institution. Results: We observed clinical clearance in 93% (66/71) of participants who received adjuvant imiquimod following surgery and 79% (19/24) in the primary non-surgical treatment group over a median of 38 months of follow-up. In the adjuvant therapy group, positive surgical margins were associated with a decreased rate of clinical clearance when compared to cases with close (<1 mm) margins or background melanocytic dysplasia (83.3 vs. 100%, p = .01). The presence of an inflammatory response during treatment was associated with increased clearance (94.1 vs. 66.7%, p = .02). Conclusions: Adjuvant imiquimod treatment may decrease LM recurrence rates in cases with background melanocytic dysplasia or close margins. LM cases with positive surgical margins need close clinical follow-up given higher recurrence rates.